An Examination of the Biosafety and Ethical Guidelines in the Science Labs at Baniwaleed University - Hammad, Abdulatti Othman; Ibrahim, Khamis Ali (Journal for Research in Applied Sciences and Biotechnology, 2022)
The aim of this study was to examine the prevalence rates of safety and work ethics in the academic laboratories of the Faculty of Science, Baniwaleed University among professors, technicians, students and workers. The data was collected through a questionnaire consisting of (11) questions applied to (30) professors, technicians, students and workers. The results showed that the majority of the segment used did not have sufficient information about safety and work ethics in the laboratories. The study produced a number of recommendations to help protect people, equipment and property in university laboratories.